Goldenhar Syndrome Associated with Extensive Arterial Malformations - Renee Frances Modica; L. Daphna Yasova Barbeau; Jennifer Co-Vu; Richard D. Beegle; Charles A. Williams (Case Reports in Pediatrics)
Goldenhar Syndrome is characterized by craniofacial, ocular and vertebral defects secondary to abnormal development of the 1st and 2nd branchial arches and vertebrae. Other findings include cardiac and vascular abnormalities. Though these associations are known, the specific anomalies are not well defined. We present a 7-month-old infant with intermittent respiratory distress that did not improve with respiratory interventions. Echocardiogram suggested a double aortic arch. Cardiac CT angiogram confirmed a right arch and aberrant, stenotic left subclavian artery, dilation of the main pulmonary artery, and agenesis of the left thyroid lobe. Repeat echocardiograms were concerning for severely dilated coronary arteries. Given dilation, a rheumatologic workup ensued, only identifying few weakly positive autoantibodies. Further imaging demonstrated narrowing of the aorta below the renal arteries and extending into the common iliac arteries and proximal femoral arteries. Given a physical exam devoid of rheumatologic findings, only weakly positive autoantibodies, normal inflammatory markers, and presence of the coronary artery dilation, the peripheral artery narrowings were not thought to be vasculitic. This case illustrates the need to identify definitive anomalies related to Goldenhar Syndrome. Although this infant’s presentation is rare, recognition of specific vascular findings will help differentiate Goldenhar Syndrome from other disease processes.